Formulation and Characterization of Nicotine Microemulsion-Loaded Fast-Dissolving Films for Smoking Cessation - Kantaporn Kheawfu; Pattaraporn Panraksa; Pensak Jantrawut (Molecules, 2022)
The present study aimed to develop a nicotine microemulsion (NCT-ME) and incorporate it into a fast-dissolving film. The NCT-ME was prepared by mixing the specified proportions of nicotine (NCT), surfactant, co-solvent, and water. The NCT-ME was measured by its average droplet size, size distribution, zeta potential, and morphology. NCT-ME fast-dissolving films were prepared by the solvent casting technique. The films were characterized by morphology, weight, thickness, disintegration time, and mechanical strength properties and the determined NCT loading efficiency and in vitro drug release. The results showed that almost all NCT-MEs presented droplet sizes of less than 100 nm with a spherical form, narrow size distribution, and zeta potentials of −10.6 to −73.7 mV. There was no difference in weight and thickness between all NCT-ME films, but significant changes in the disintegration times were noticed in NCT40-Smix[PEG-40H(2:1)]10 film. The mechanical properties of films varied with changes in type of surfactant. About 80% of the drug release was observed to be between 3 and 30 min. The drug release kinetics were fitted with the Higuchi matrix model. The NCT40-Smix[P-80(1:1)]10 film showed the highest dissolution rate. It was concluded that the developed ME-loaded fast-dissolving film can increase drug release to a greater extent than the films without ME.